Assessment of Prevalence of Cardiovascular Risk in Diabetic Patients Attending OPD of Chitwan Medical College Teaching Hospital - Bijay Aryal, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Assessment of Prevalence of Cardiovascular Risk in Diabetic Patients Attending OPD of Chitwan Medical College Teaching Hospital